(untitled) (Global Journal of Science Frontier Research, 2017)
In this paper we study a new subclass of harmonic univalent functions defined by q-calculus coefficient inequalities, distortion, bounds, extreme point, convolution, convex combination are determined for this class. Finally we discuss a class preserving integral operator and q- Jackson’s type integral for this class.